MASHLAHAH SEBAGAI TUJUAN INTI PEMBENTUKAN HUKUM ISLAM - Sulthon, Muhammad (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2023)
Abstract All provisions of syara' law must lead to the aspect of mashlahah. There is almost no provision of Allah's law that is "quiet" from maslahah. And it can even be said that mashlahah is the key to being able to understand the intentions and messages of syari' contained in syar'i texts. Therefore, since the beginning of Islamic sharia (the provisions of syara' law) actually did not have any other basis (goal) except for human benefit. A legal provision which denies human benefit, will undoubtedly conflict with universal human values. Because only with this benefit will we be able to prove that Islamic shalihun li kulli Zaman wa eats. The method used in this research is based on literature review. The data collected is based on searching several documents, literature, scientific journals related to the context of this study. The analysis was carried out descriptively. The results of the study found that the essence of mashlalah is; al-muhafadhatu 'ala maqsud al-syar'i "Maintaining syara' goals (in establishing law)". And the purpose of sharia in establishing law is five, namely, maintaining religion, soul, mind, lineage, and wealth. Keywords: Mashlahah, core purpose, formation, Islamic law.